นิเวศวิทยาการเมืองเชิงพุทธกับการปลูกฝังวัฒนธรรมประชาธิปไตยในโรงเรียน - (เสนศรี), พระมหาฉัตรเพชร สุภทฺโท; (เจติยะ), พระมหามนัส ปญฺญาวุฑฺโฒ; โทอื้น, วรเชษฐ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This article, “Buddhist Political Ecology and the Cultivation of Democratic Culture in Schools,” aims to explore the interrelationship between the concept of political ecology and Buddhist principles in order to construct a new conceptual framework for cultivating democratic culture sustainably within the context of Thai education. It posits that democracy should not be viewed merely as a political system but as a holistic way of life that integrates the human relationship with social, political, and spiritual environments. The framework of Buddhist political ecology emphasizes the doctrine of paticcasamuppada (dependent origination), highlighting the interconnectedness between individuals, communities, and educational institutions. This leads to an understanding of democracy as a “moral ecosystem” grounded in compassion, wisdom, and responsibility. At the school level, the cultivation of democratic culture based on this perspective goes beyond teaching rights, duties, or political rules. It focuses on creating a “mindful space for coexistence” in which students actively participate through learning processes that integrate Buddhist teachings such as sila (morality), samadhi (concentration), and panna (wisdom) with civic and social education. This integrative approach nurtures students’ attitudes of respect, empathy, cooperation, and compassion, which are the essential foundations of genuine democracy. The analysis suggests that fostering democratic culture in schools through the lens of Buddhist political ecology establishes a “learning ecosystem” that bridges morality and politics in practice. It also opens new dimensions of Buddhist political science by emphasizing the development of both “inner citizenship” and “outer citizenship,” allowing politics to become a means for social harmony rather than a struggle for power. This framework provides theoretical and practical implications for educational policy development aimed at promoting consciousness-based education and sustainable democratic citizenship in Thai society.